Activation of peroxymonosulfate by nitrogen-doped carbocatalysts derived from brown algal (Sargassum duplicatum) for the degradation of polycyclic aromatic hydrocarbons in marine sediments. Issue 6 (December 2021) - Hung, Chang-Mao; Chen, Chiu-Wen; Huang, Chin-Pao; Dong, Cheng-Di
Abstract: A novel nitrogen-enrich biochar carbocatalyst (BAB) was derived from brown algal ( Sargassum duplicatum ) as precursor by direct pyrolyzation at 300–900 °C. Heteroatom nitrogen doping and the nitrogen functionality of the metal free carbocatalyst activated PMS and produced abundant reactive species (ROSs). BAB and melamine pyrolysis product (N-BAB) effectively activated peroxymonosulfate (PMS) that resulted in the radical and nonradical-based oxidation of 2- to 6-ring polycyclic aromatic hydrocarbons (PAHs). The catalyst N-BAB enabled 86% of PAHs removal in 12 h under optimal conditions ([PMS] = 1 × 10 -4 M, [N-BAB] = 3.3 g/L, and pH 3.0), and 56%, 72%, 76%, 82%, and 70% removal of 2-, 3-, 4-, 5-, and 6-ring PAHs, respectively. The graphitization and nitrogen functionalization of biochar matrixes brought about rich defects and edges as radical/singlet oxygen-mediated oxidation sites, which resulted in enhancing the catalytic efficiency during PMS activation for PAHs degradation. The PAHs degradation were faster in N-BAB/PMS (observed rate constant, k obs, rate of 9.8 × 10 -2 h -1 ) than in the BAB/PMS (6.6 × 10 -2 h -1 ) system. Results of electron paramagnetic resonance (EPR) analysis revealed that both radical (SO4 - and HO) and nonradical ( 1 O2 ) pathways on the N-functionalized carbocatalyst facilitated PAHs degradation. The results showed also that N-doped biochar exhibited great potential in the remediation of sediment matrices and that the carbocatalyst-PMS process developed in the present study was highly efficient, simple to implement, and cost-effective for providing added value to natural biomass by using advanced biochar activation of PMS. Graphical Abstract: ga1 Highlights: Brown algal biochar was used to activate peroxymonosulfate for PAHs removal. The catalytic system performed effectively at a wide pH range (3.0–11.0). Synergistic effects between N and C species facilitated the production of ROSs. Nitrogen-doped BAB enhanced PAH degradation due to additional SO4 –, HO, and 1 O2 . The PAHs degradation mechanism and kinetics were elucidated.